AB0140 BAFF NEUTRALIZATION HAS JANUS-FACED EFFECT ON ATHEROSCLEROSIS ASSOCIATED WITH SYSTEMIC LUPUS ERYTHEMATOSUS. (13th June 2020) - Saidoune, F.; Charles, N.; Chezel, J.; Escoubet, B.; Papo, T.; Nicoletti, A.; Sacre, K.
Abstract : Background: Cardiovascular diseases (CVD) are the leading cause of death in systemic lupus erythematosus (SLE). B cells play a key role in the pathogenesis of lupus and anti-BAFF therapy has been approved in SLE. Since mature B cells also promote atherosclerosis, BAFF neutralization is expected to have an atheroprotective effect in SLE. Objectives: The aim of our study was to test this hypothesis using a new mouse model with a mix susceptibility to lupus and atherosclerosis that received or not an anti-BAFF treatment, and in a cohort of SLE patients in whom we monitored carotid plaques, the B cell compartment and BAFF levels. Methods: The effect of BAFF on atherosclerosis associated with lupus was investigated in the atherosclerosis- and lupus-prone Apoe°D227K mouse model and in a cohort of SLE patients. Mice were treated with a blocking anti-BAFF monoclonal antibody (Ab), while fed with a standard chow diet. Carotid plaque and carotid intima media thickness were assessed by ultrasound at baseline and during follow-up in SLE patients asymptomatic for CVD. Results: Anti-BAFF Ab in Apoe°D227K mice i/ induced a B cell depletion, ii/ efficiently treated lupus, iii/ improved atherosclerosis lesions in mice that had low plasma cholesterol levels but worsened the lesions in mice with high cholesterol levels. In that case, the atheroprotective effect of the BAFF-BAFFR signaling inhibition on B cells was counterbalanced by the proatherogenic effect of the BAFF-TACI signaling inhibition on macrophages. In SLE patients, BAFF blood levels were associated with subclinical atherosclerosis. Anti-BAFF Ab treatment had a differential effect on the intima media thickness progression in SLE patients depending on the body mass index Conclusion: Depending on the balance between metabolic- and B cell-induced proatherogenic conditions, anti-BAFF could be respectively detrimental or beneficial on atherosclerosis development in SLE Acknowledgments: Guillaume Even, Yasmine Lamri, Anh-Thu Gaston, Disclosure of Interests: Fanny Saidoune Grant/research support from: supported by a research partnerships between the academic and GlaxoSmithKline France. Anti-BAFF mAb (IgG1, clone 10F4B) in mice was provided by Glaxosmithkline, Nicolas Charles: None declared, Julie Chezel: None declared, Brigitte Escoubet: None declared, Thomas Papo: None declared, Antonino Nicoletti: None declared, karim sacre: None declared